PENGARUH METODE CIRCUIT TRAINING TERHADAP PENINGKATAN KETERAMPILAN PUKULAN SMASH DALAM BULU TANGKIS EKSTRAKURIKULER DI SMAN 2 SUKATANI - Muhammad Alvito Ramadhani; Suprananto; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the circuit training method on improving smash skills in badminton among extracurricular students at SMAN 2 Sukatani. The background of this research lies in the importance of the smash technique as a primary offensive move in badminton, along with the need for a structured and effective training method to enhance this ability. The circuit training method was selected for its potential to develop strength, endurance, agility, and overall body coordination. This research employed a quantitative approach with a One Group Pretest-Posttest Design. The sample consisted of 30 badminton extracurricular students, selected using total sampling. The instrument used was a practical test of smash skills, covering initial stance, execution, and follow-through phases. Data were collected through a pre-test before treatment and a post-test after eight sessions of circuit training. Data analysis was conducted using descriptive statistics and a paired sample t-test with the assistance of SPSS 25. The results showed an increase in the average score from 9.10 in the pre-test to 11.20 in the post-test. The t-test results revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between pre-test and post-test scores. It can be concluded that the circuit training method has a significant effect on improving smash skills in badminton. This method is recommended to be implemented in extracurricular training programs as it effectively enhances students’ overall performance. The findings also contribute to the development of structured physical education training strategies.